Perilaku Pemberian Asi Ekslusif di Puskesmas Bara-Baraya Kota Makassar - Nurdiyanah Nurdiyanah; Nildawati Nildawati (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2015)
One important aspect on children’s growth is started from early child-period by giving 6 month-exclusive breast feeding. Therefore, this research was aimed to examine exclusive breast-feeding behaviors among mothers in Puskesmas Bara-Baraya Makassar. Data were collected using purposive random sampling by reaching 56 mothers who have children age 0-12 months in Puskesmas Bara-Baraya Makassar. The results showed that majority of the mothers, 67, 86%, were having good knowledge of exclusive breast feeding, and 32,14% were less knowledge of exclusive breast feeding. However, in term of perception, 67,86% of the mothers were having negative perception on breast feeding, and 32,14% of the mothers were having a positive perception on breast feeding. Although, in term of practice, 60.71% of the mothers were having good practice of exclusive breast feeding and only 39, 29% are less good. Based on those results, there is still a need for health education to increase knowledge and to change negative perception among mothers, about exclusive breast feeding to gain better health for children and for the mothers itself.